Reproductive Performance of female of Cryphiops caementarius (Crustacea: Palaemonidae) maintained with natural food - Bazán, Magali (2009)
The aim was to determine the reproductive performance of females of C. caementarius maintained with natural food. Twenty four females inmature were used (5,2 cm and 2,0 g), conditioned in eight aquarium (50 l) and fed during two months according to each treatment, with giant squid (Dosidicus sp), clam (Semele solid), polychaete (Pseudonereis sp.) and with balanced. The reproductive performance of females was improved when fed with polychaete and giant squid, achieving maturation between 16 to 18 days with higher fecundity (2627 and 1378 eggs g-1) and fertility (2566 and 1364 larvae g-1, respectively).